Cartilla para Desarrollar un Plan de Negocio Agrícola - Edward A. Evans (EDIS, 2009)
FE819, a 3-page fact sheet by Edward A. Evans, is the Spanish language version of FE720: Primer for Developing a Farm Business Plan, the first of the Agribusiness Primer series. It provides an overview of developing a business plan. It identifies the main components of a business plan and reiterates why you should develop one. Includes references. Published by the UF Department of Food and Resource Economics, November 2009.